Physiological and Neurophysiological Effects of Sports Massage on the Athletes' Performance: A Review Study - Hasan Shamsi; Farshad Okhovatian; khosro khademi Kalantari (Shahid Beheshti University of Medical Sciences, 2022)
Background and Aims: Massage therapy is widely used by athletes for various reasons such as recovery from fatigue, preventing injury, and relaxation. It is believed that massage improves the performance of the athletes by increasing their blood flow, removing lactic acid, and stimulating the nervous system. This review study aims to investigate the physiological and neurophysiological effects of sports massage on the athletes' performance, to find out whether the clinical beliefs of sports physiotherapists about the effects of sports massage on sports injuries are supported by scientific evidence or not.Methods: In this review study, a search was conducted in Google Scholar PubMed, and ScienceDirect databases on studies published in English from 1975 to 2020 using the keywords: Sports massage, sports injuries, physiological mechanisms, neurophysiological mechanisms, and performance of athletes. Fifty articles about the effects of sports massage were assessed for eligibility. Finally, 14 clinical trial studies and one case report study were included in the review.Results: Few studies have been conducted on the effect of sports massage on the athletes' performance. The existing studies are heterogeneous, i.e., they have examined the effect of massage on different factors and reported contradictory results. It seems that the effects of sports massage on the athletes' performance are more due to its psychological effects rather than its clinical effects. The effects of sports massage on athletes' performance have not yet been supported by scientific evidence.Conclusion: Many scholars consider that the effects of sports massage are due to increasing blood flow, but there is insufficient scientific evidence. In treatment of tendonitis and muscle strains, there is insufficient evidence that sports massage can reduce pain and accelerate healing. It seems the therapeutic effects of sport massage are more psychological and less physiological.